Prevalence of Non-Alcoholic Fatty Liver Disease in Kidney Donors at Pakistan Kidney and Liver Institute and Research Center (PKLI&RC) Lahore - Ahmar Ijaz, Adil Manzoor, Falak Shan, Husham Ahmad, Irsa Andleeb, Muhammad Bilal Basit (Pakistan Journal of Medical & Health Sciences, 2022)
As the incidence of having a fatty liver on ultrasound is increasing in the east due to the unhealthy dietary habits resulting due to the influence of west, it is important to diagnose people who are willing to become kidney donors. The future risk of diabetes and developing the metabolic syndrome is not uncommon in this population who will be already devoid of one kidney. The increase in morbidity and mortality in such population due to cardiovascular causes can’t be ignored. This retrospective observational study having a sample size of 200 was conducted at a specialized center in Pakistan. Patients having NAFLD due to any other causes such as hepatitis, alcoholism or any drug were excluded. Data was collected after the approval of the research and ethical board. All the data was entered into SPSS version 22 and analyzed. P value of <0.05 was taken as significant. Results revealed 55% male population and participants had an average age of 36.8±10.1 years, BMI 26.4±4.3 kg/m2, HbA1c 5.33±0.34, uric acid 5.1±1.4 mg/dl, triglyceride 138±80 mg/dl. The prevalence of NAFLD was 30%. A significant association was found out between presence of NAFLD and age, BMI and triglyceride levels with a p-values 0.011, 0.001 and 0.002 respectively. This data was compared with similar studies and comparable results were observed. Keywords: kidney donors, NAFLD, diabetes